Survey on the Importance of Mange in the Aetiology of Skin Lesions in Goats in Peninsular Malaysia - Dorny, Pierre; T., Van Wyngaarden; Vercruysse, Jozef; Symoens, Chantal; Abu, Jalila (Springerlink, 1994)
A survey on mange mite infestations in the aetiology of skin lesions in goats in Peninsular Malaysia is described. Skinlesions were observed in 25 (93%) of the 27 goat farms investigated. Mange mites were found in 22 (88%) of these goat herds. Chorioptes texanus was found in 20.7%, Psoroptes cuniculi in 19-3%, Sarcoptes scabiei in 18.6% and Demodex canis var. caprae in 0.4% of the samples, taken from the skin lesions. Thirteen cases of generalised mange were diagnosed, from which 9 were caused by S. scabiei, 2 by P. cuniculi and one by C. texanus. All other cases had more or less localised lesions. No significant differences could be found in incidence and distribution of skin lesions between age classes.